Desain Game 2D Mini Zoo Edukasi Interaktif untuk Anak-Anak Usia 7 Tahun Keatas - Siamboro, Febri; Pertiwi, Ratih (Indo-MathEdu Intellectuals Journal, 2024)
This research focuses on the development of 2D Mini Zoo games specifically designed for children aged 7 years and above. By combining jigsaw puzzle game elements and square puzzles, the game aims to create a fun and rewarding learning experience. The approach used in this study is a qualitative approach. The data collected from these observations and interviews is expected to be authentically integrated in game development. Data analysis was carried out qualitatively consisting of data reduction, data presentation and conclusion drawing. The results of the study show that through this game, children can learn to recognize shapes and animals in an interactive and colorful way. The friendly and attractive visual design was deliberately chosen to make children feel comfortable and interested in continuing to play while learning. In addition, this game also helps children in developing important skills such as eye-hand coordination, memory, and problem-solving skills. We hope that Mini Zoo can be a fun learning companion for children, helping them grow and develop in a supportive and educational environment